Comparative Study of Intercession from the Perspective of Transcendental Wisdom, Ash’arism (Based on the Views of Fakhr al-Razi) and Mo’tazila (Based on the Views of Qazi Abdul Jabbar) in Terms of the Noble Quran - morteza Bayat; mahmood saidiy; ehsan mansoori (پژوهش‌های تفسیر تطبیقی, 2018)
Intercession is one of exegetic-theological issues raised among Islamic thinkers through the verses of the Quran. Intercessory issues can be divided into two general categories as those who intercede and those who are interceded. ‘Ashari and Mo’tazila theologies regard Prophet Muhammad as an intercessor, yet have not commented anything special about other intercessors. In contrast, Mulla Sadra regards pioneer creatures in the curve of descent (Rational Abstracts) and those in the curve of ascent (Complete Humans) as intercessors and leaders for the rest of humans in their path to God because of being mediators to receive grace. The Prophet of Islam initiates intercession due to his comprehensive features. Mo’tazila holds that intercession would increase the blessing of Muminin in paradise and ‘Asharism holds that it would also decrease the punishment of fasiqin (violators) and cruel people. Criticizing Mo’tazila theology, Mulla Sadra regards intercession as also effective in reducing the punishment of those doomed to hell; of course just in case their vicious acts are not dominant.